LAW ENFORCEMENT AGAINST CORRUPTION IN PERSPECTIVE OF HUMAN RIGHTS IN INDONESIA - Sekhroni Sekhroni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption has a correlation with Human Rights (HAM) correlations are both very clear, because in almost all cases of corruption, directly or indirectly, will be followed by human rights violations. Acts of corruption always starts from the abuse of power, which means that the perpetrators of corruption are usually carried out by the holders of power. In other words, that the deviant act committed by the bureaucracy in the form of corruption, can create misery for poor people in a country. That means the act of corruption has taken place the deprivation of the rights of the public on the economic, social and cultural, that means there has been a violation of Human Rights.